Pengaruh Family Support terhadap Financial Resilience Mahasiswa Rantau dengan Financial Self-Efficacy sebagai Pemoderasi - Wicaksana, Febrian Eka Candra; Yuhertiana, Indrawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Overseas students are a group of individuals who face complex challenges in adapting to a new environment, particularly in terms of financial management. Living far from their families demands a high level of independence in academic, social, and economic aspects. This study aims to examine and analyze the effect of family support on the financial resilience of overseas students, with financial self-efficacy as a moderating variable. The research was conducted at Asrama Mahasiswa Nusantara Surabaya with a total of 80 respondents selected through random sampling. The research method used was quantitative with a survey approach, and data analysis was carried out using the PLS-SEM technique through SmartPLS 4.0 software. The results show that family support (p = 0.000; t = 10.914) and financial self-efficacy (p = 0.015; t = 2.213) have a significant effect on the financial resilience of overseas students. However, financial self-efficacy (p = 0.401; t = 0.252) does not moderate the relationship between family support and financial resilience significantly. These findings indicate that students tend to rely more on family support as the main source of financial stability, while confidence in financial aspects has not yet developed optimally during their period of living away from home.